Composite current collector base membrane, manufacturing method and secondary battery

Through the three-layer co-extrusion process and multi-layer aluminum plating technology, the problem of the decrease in the bonding force of the metal layer and the polymer layer in the secondary battery is solved, and the safety and performance stability of the battery are improved.

CN119252928APending Publication Date: 2025-01-03JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411527074.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In secondary batteries, electrolyte penetration causes the chemical bond between the metal layer and the polymer layer to be destroyed, and the binding force decreases, affecting the battery performance and safety, and the polymer base layer swells in the organic solvent, further reducing the binding force.

Method used

The composite fluid-collection base film is prepared by a three-layer co-extrusion process. Through the combination of polymer layer, improved layer and heat-shrinkable particles, the contact area between the metal layer and the polymer layer is increased, and a multi-layer aluminum plating is formed by evaporative aluminum plating to improve the Binding power.

Benefits of technology

The binding force between the polymer layer and the metal layer is significantly improved, the swelling and aging problem is slowed down, the binding force between the active substance and the composite fluid is enhanced, and the safety and performance stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252928A_ABST
    Figure CN119252928A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite current collector base membrane, a manufacturing method and a secondary battery. According to the invention, high-molecular polymers (such as polyolefins, polyesters and polyurethane) are added as the high-molecular layer, and an improved high-molecular polyester material is added as the improved layer, so that the film substrate is prepared. Spraying the thermal shrinkage particles to the surface of the film substrate to obtain a composite current collector base film; and fixing the composite current collector base film, winding and unwinding the composite current collector base film, adjusting tension, vacuumizing, and evaporating and aluminizing for 15 times to obtain a finished product. The prepared finished product can effectively improve the contact area of the polymer layer and metal, so that the binding force of the polymer layer and the metal layer is improved, and the mechanical stability and durability of the whole composite structure are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, in particular to a composite current collector base film and a manufacturing method thereof and a secondary battery. Background Art

[0002] The current collector refers to a structure or part used to collect current. In secondary batteries, the main function of the current collector is to collect the current generated by the active material of the battery so as to output a larger current to the outside. Common current collectors include metal foil, composite current collectors, etc. Compared with traditional current collectors (such as aluminum foil or copper foil), composite current collectors have the advantages of reducing metal usage, improving energy density and safety, and therefore have broad application prospects in secondary batteries. The preparation of composite current collectors is usually to deposit a metal copper or aluminum layer with a thickness of about 1 micron on a polymer substrate (such as polyolefin, polyester, polyimide). Since the polymer substrate and the metal layers on both sides constitute a composite current collector, this structure can effectively reduce costs, improve safety and increase energy density. When the battery is short-circuited, the insulating support layer and the special "sandwich" flame-retardant structure of the composite current collector can produce extremely high resistance, thereby effectively reducing the possibility of thermal runaway of the battery. At the same time, the composite current collector uses an insulating support layer to replace part of the metal, which greatly reduces the weight of the current collector, thereby improving the energy density of the battery and reducing the cost of raw materials. Therefore, the composite current collector has received widespread attention in recent years.

[0003] However, during the long-term use of secondary batteries, the electrolyte may penetrate into the metal layer of the composite current collector. The organic solvent of the electrolyte will destroy the chemical bond between the metal layer and the metal oxide layer, causing the bonding force between the two layers to gradually weaken, resulting in the metal layer falling off from the polymer layer. This shedding phenomenon will not only affect the positive and negative electrode interfaces inside the battery, but also cause the electrical performance of the battery to deteriorate and may affect the safety of the battery. In addition, the polymer base layer (mainly composed of materials such as polyolefins, polyesters, polyimides, etc.) will swell when immersed in organic solvents for a long time, causing the bonding force between the polymer layer and the metal layer to further decrease.

[0004] In order to overcome the defects of the prior art, the present invention provides a composite current collector and a manufacturing method thereof and a secondary battery. Summary of the invention

[0005] The object of the present invention is to provide a composite current collector base film and a manufacturing method and a secondary battery to solve the problems in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] The method for preparing a composite current collector base film comprises the following steps: mixing polyethylene terephthalate, a lubricant, a coupling agent and an inorganic powder to obtain a polymer layer raw material; mixing furan-based polyester, a lubricant, a coupling agent and an inorganic powder to obtain a modified layer raw material; preparing the polymer layer raw material and the modified layer raw material through a three-layer co-extrusion process to obtain a film substrate, wherein the film substrate has a polymer layer as an intermediate layer and modified layers on both sides; spraying heat shrinkable particles onto the surface of the film substrate, cooling, solidifying and pulling to obtain a composite current collector base film.

[0008] More optimally, the contents of the components of the polymer layer raw materials are: by mass fraction, 70wt%-90wt% polyethylene terephthalate, 0-8wt% lubricant, 0-2.5wt% inorganic powder, and the balance is a coupling agent; the contents of the components of the modified layer raw materials are: by mass fraction, 80wt%-90wt% furan-based polyester, 0-10wt% lubricant, 0-3wt% inorganic powder, and the balance is a coupling agent; the lubricant is stearic acid and trihydroxystearate, the coupling agent is a titanate coupling agent, and the inorganic powder is ultrafine calcium carbonate and graphene.

[0009] More optimally, the three-layer co-extrusion blown film technology is to coat different materials in the order of high-toughness inner wall layer, middle pressure-resistant layer and scratch-resistant outer wall layer from the inside to the outside, and then weigh the raw materials respectively and add them to the inner, middle and outer film blowing devices in sequence; during the film blowing process, the temperature of each section of the outer, middle and inner zones of the film blowing device is controlled to be 200-220℃, the main screw speed of the film blowing device is adjusted to 240-300r / min, the traction speed is 7-10m / min, and the blowing ratio is 3-4.

[0010] More optimally, the thickness of the modified layer is 0.5-1.0 mm, and the thickness of the polymer layer is 4.0-5.0 mm.

[0011] More optimally, the preparation process of the heat shrinkable particles is as follows: polyethylene terephthalate resin, diethylene glycol and acetaldehyde are mixed to obtain a preform; the preform is heated and melted, extruded through a specific mold, stretched radially into a long strip, kept in its expanded state and rapidly cooled to room temperature to obtain a strip material; the strip material is crushed and processed into heat shrinkable particles with a diameter of 10-100nm; wherein as cooling occurs, the transition component is reorganized into crystallites; the elastic component and amorphous chain are stretched in an expanded state, and rapid cooling causes the movement of the amorphous chain to be obstructed or restricted, thereby locking it in its expanded state.

[0012] More optimally, 80-90 wt % of polyethylene terephthalate resin, 1-5 wt % of diethylene glycol, and 1-5 wt % of acetaldehyde are mixed to obtain a prefabricated material.

[0013] More optimized, spraying parameters: spraying pressure 25-40N / cm 2 , gun distance 20-30cm, spraying temperature 225-240℃; cooling and curing parameters: cooling roller temperature 20-30℃, traction force 100-120N.

[0014] A method for making a composite current collector, comprising: performing metal plating on both sides of a composite current collector base film made by the method to obtain a composite current collector; during metal plating, the metal used includes but is not limited to metal copper and metal aluminum; the plating process used includes but is not limited to evaporation process, magnetron sputtering process, electroplating process, and chemical plating process.

[0015] More optimally, the composite current collector base film is fixed on both sides, vacuumed, and aluminum is evaporated on the surface to obtain the composite current collector; the vacuum degree of the vacuum treatment process is 5×10 -3 -5.5×10 -3 Pa; the tension adjustment range when the film is fixed is: the tension of the film unwinding end is set to 130-140N, and the tension of the winding end is set to 100-110N.; The evaporation aluminum plating process is specifically as follows: the composite current collector base film is fixed on the winding trolley, the winding trolley is started in a vacuum environment, the speed of the winding trolley is set to 260-300m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 400-500mm / min, and finally a uniform aluminum plating layer is formed on the composite current collector base film.

[0016] The battery prepared by the composite current collector comprises a cathode, an anode, a shell and an electrolyte layer between the cathode and the anode; wherein the cathode comprises a composite current collector and an active material layer coated on the surface of the composite current collector.

[0017] Beneficial effects of the present invention:

[0018] The composite current collector prepared by the present invention includes a polymer layer, a modified layer, and a metal conductive layer. The present invention prepares a film substrate by adding a polymer (such as polyolefins, polyesters, and polyurethanes) as a polymer layer and adding a modified polymer polyester material as a modified layer. The heat shrinkable particles are sprayed onto the surface of the film substrate to obtain a composite current collector base film; the composite current collector base film is subjected to film fixing, film retraction and release, tension adjustment, vacuuming, and aluminum evaporation 15 times to obtain a finished product. Among them, heat shrinkable particle materials are added to the modified layer, and the heat shrinkable particles shrink during the composite current collector coating process to form heat shrinkage holes of different diameters on the substrate layer, thereby increasing the contact area between the polymer layer and the metal conductive layer to improve the bonding force. The present invention is based on the purpose of improving the bonding force between the metal layer of the composite current collector and the polymer, combined with the current composite current collector coating equipment and process, by improving the contact area between the polymer layer and the metal and the material of the polymer layer, thereby significantly improving the bonding force between the polymer layer and the metal layer.

[0019] The present invention has the following advantages:

[0020] 1. The improved layer in the composite current collector of the present invention can solve the swelling phenomenon of the polymer layer in the organic solvent of the electrolyte, and alleviate the problem of the continuous deterioration of the bonding force between the metal conductive layer and the polymer layer caused by the swelling and aging of the polymer layer.

[0021] 2. The composite current collector of the present invention forms concave holes of different diameters on the surface of the metal plating layer, thereby increasing the binding force between the active material layer and the composite current collector, making it difficult for the active material of the electrode to fall off.

[0022] 3. Compared with the traditional composite current collector, the composite current collector of the present invention reduces the metal oxide layer of the polymer layer and the metal conductive layer, optimizes the process and improves the production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0024] Figure 1 It is a schematic diagram of the structure of the composite current collector of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Source of raw materials:

[0027] Polyethylene terephthalate resin, provided by Yihua Dongli Polyester Film Co., Ltd., model 120-55-8DEDB; furan-based polyester, provided by Yihua Dongli Polyester Film Co., Ltd., model 3238-40-2; PET base film, provided by Yihua Dongli Polyester Film Co., Ltd., model XH40H; ultrafine calcium carbonate particle size is 320 mesh; titanate coupling agent, provided by Nanjing Xuanhao New Materials Technology Co., Ltd., model NXH-201.

[0028] Example 1: Step 1: The preparation process of heat shrinkable particles is as follows: 90wt% polyethylene terephthalate resin, 5wt% diethylene glycol, and 5wt% acetaldehyde are mixed to obtain a preform; the preform is heated, melted, extruded, stretched from the radial direction into a long strip, and then quickly cooled to room temperature to obtain a strip material; and the strip material is crushed into heat shrinkable particles with a diameter of 25nm;

[0029] In terms of mass fraction, 85wt% polyethylene terephthalate resin, 8wt% stearic acid, 2.5wt% ultrafine calcium carbonate, and 4.5wt% titanate coupling agent are mixed to obtain a polymer layer raw material; 85wt% furan-based polyester, 5wt% stearic acid, 2.5wt% ultrafine calcium carbonate, and 7.5wt% titanate coupling agent are mixed to obtain a modified layer raw material; the polymer layer raw material and the modified layer raw material are prepared by a three-layer co-extrusion process to obtain a film substrate; heat shrinkable particles are sprayed onto the surface of the film substrate, and after cooling, solidification, and pulling, a composite current collector base film is obtained; the film substrate has a polymer layer as an intermediate layer and modified layers on both sides, wherein the thickness of the modified layer is 0.5mm, and the thickness of the polymer layer is 5mm;

[0030] The three-layer co-extrusion process uses the three-layer co-extrusion film blowing technology. The temperature of the outer, middle and inner zones in the film blowing device is set to 220°C, the main engine screw speed is set to 300r / min, the traction speed is 10m / min, and the inflation ratio is 4; spraying parameters: spraying air pressure 40N / cm 2 , gun distance 30cm, spraying temperature 240℃; cooling and curing parameters: cooling roller temperature 30℃, traction force 120N;

[0031] Step 2: Fix the composite current collector base film, retract and release the film, adjust the tension, evacuate, evaporate and aluminum to obtain an aluminum coating, repeat the above steps 15 times to form 15 layers of aluminum coating to obtain a finished product; the tension adjustment range is: the tension of the film release end is set to 130N, and the tension of the winding end is set to 100N; the vacuum degree of the vacuum treatment process is 5×10 - 3Pa; The specific evaporation aluminum plating process is as follows: the composite current collector base film is fixed on the winding trolley, the winding trolley is started in a vacuum environment, the winding trolley speed is set to 300m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 500mm / min, and finally a uniform aluminum coating is formed on the composite current collector base film.

[0032] Example 2: Adjusting the diameter of heat shrinkable particles to 100 nm: Step 1: The preparation process of heat shrinkable particles is as follows: 90 wt% polyethylene terephthalate resin, 5 wt% diethylene glycol, and 5 wt% acetaldehyde are mixed to obtain a preform; the preform is heated, melted, extruded, stretched from the radial direction into a long strip, and then quickly cooled to room temperature to obtain a strip material; and the strip material is crushed into heat shrinkable particles with a diameter of 100 nm;

[0033] In terms of mass fraction, 85wt% polyethylene terephthalate resin, 8wt% stearic acid, 2.5wt% ultrafine calcium carbonate, and 4.5wt% titanate coupling agent are mixed to obtain a polymer layer raw material; 85wt% furan-based polyester, 5wt% stearic acid, 2.5wt% ultrafine calcium carbonate, and 7.5wt% titanate coupling agent are mixed to obtain a modified layer raw material; the polymer layer raw material and the modified layer raw material are prepared by a three-layer co-extrusion process to obtain a film substrate; heat shrinkable particles are sprayed onto the surface of the film substrate, and after cooling, solidification, and pulling, a composite current collector base film is obtained; the film substrate has a polymer layer as an intermediate layer and modified layers on both sides, wherein the thickness of the modified layer is 0.5mm, and the thickness of the polymer layer is 5mm;

[0034] The three-layer co-extrusion process uses the three-layer co-extrusion film blowing technology. The temperature of the outer, middle and inner zones in the film blowing device is set to 220°C, the main engine screw speed is set to 300r / min, the traction speed is 10m / min, and the inflation ratio is 4; spraying parameters: spraying air pressure 40N / cm 2 , gun distance 30cm, spraying temperature 240℃; cooling and curing parameters: cooling roller temperature 30℃, traction force 120N;

[0035] Step 2: Fix the composite current collector base film, retract and release the film, adjust the tension, evacuate, evaporate and aluminum to obtain an aluminum coating, repeat the above steps 15 times to form 15 layers of aluminum coating to obtain a finished product; the tension adjustment range is: the tension of the film release end is set to 130N, and the tension of the winding end is set to 100N; the vacuum degree of the vacuum treatment process is 5×10 - 3Pa; The specific evaporation aluminum plating process is as follows: the composite current collector base film is fixed on the winding trolley, the winding trolley is started in a vacuum environment, the winding trolley speed is set to 300m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 500mm / min, and finally a uniform aluminum coating is formed on the composite current collector base film.

[0036] Example 3: The thickness of the modified layer is adjusted to 1 mm, and the thickness of the polymer layer is adjusted to 4 mm: Step 1: The preparation process of heat shrinkable particles is: 90 wt% polyethylene terephthalate resin, 5 wt% diethylene glycol, and 5 wt% acetaldehyde are mixed to obtain a preform; the preform is heated, melted, extruded, stretched from the radial direction into a long strip, and then quickly cooled to room temperature to obtain a strip material; and the strip material is crushed into heat shrinkable particles with a diameter of 10-100 nm;

[0037] In terms of mass fraction, 85wt% of polyethylene terephthalate resin, 8wt% of stearic acid, 2.5wt% of ultrafine calcium carbonate, and 4.5wt% of titanate coupling agent are mixed to obtain a polymer layer raw material; 85wt% of furan-based polyester, 5wt% of stearic acid, 2.5wt% of ultrafine calcium carbonate, and 7.5wt% of titanate coupling agent are mixed to obtain a modified layer raw material; the polymer layer raw material and the modified layer raw material are prepared by a three-layer co-extrusion process to obtain a film substrate; heat shrinkable particles are sprayed onto the surface of the film substrate, and after cooling, solidification, and pulling, a composite current collector base film is obtained; the film substrate has a polymer layer as an intermediate layer and modified layers on both sides, wherein the thickness of the modified layer is 1mm and the thickness of the polymer layer is 4mm;

[0038] The three-layer co-extrusion process uses the three-layer co-extrusion film blowing technology. The temperature of the outer, middle and inner zones in the film blowing device is set to 220°C, the main engine screw speed is set to 300r / min, the traction speed is 10m / min, and the inflation ratio is 4; spraying parameters: spraying air pressure 40N / cm 2 , gun distance 30cm, spraying temperature 240℃; cooling and curing parameters: cooling roller temperature 30℃, traction force 120N;

[0039] Step 2: Fix the composite current collector base film, retract and release the film, adjust the tension, evacuate, evaporate and aluminum to obtain an aluminum coating, repeat the above steps 15 times to form 15 layers of aluminum coating to obtain a finished product; the tension adjustment range is: the tension of the film release end is set to 130N, and the tension of the winding end is set to 100N; the vacuum degree of the vacuum treatment process is 5×10 - 3Pa; The specific evaporation aluminum plating process is as follows: the composite current collector base film is fixed on the winding trolley, the winding trolley is started in a vacuum environment, the winding trolley speed is set to 300m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 500mm / min, and finally a uniform aluminum coating is formed on the composite current collector base film.

[0040] Comparative Example 1: The composite current collector base film is replaced with a PET base film containing a metal oxide layer, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The PET base film is sequentially subjected to film fixing, film retraction and release, tension adjustment, vacuuming, evaporation aluminum plating, and oxygenation to obtain a PET base film containing a metal oxide layer; wherein the tension adjustment range is: the tension of the film release end is set to 130N, and the tension of the winding end is set to 100N; the vacuum degree of the vacuum treatment process is 5×10 -3 Pa; The specific evaporation aluminum plating process is as follows: the PET base film is fixed on the winding trolley, the winding trolley is started in a vacuum environment, the speed of the winding trolley is set to 500m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 80mm / min, and finally a uniform aluminum coating is formed on the PET base film; oxygen flow parameters: oxygen flow rate 2000sccm;

[0041] Step 2: Fix the PET base film containing the metal oxide layer, retract and release the film, adjust the tension, evacuate, evaporate and aluminum to obtain an aluminum coating, and repeat the above steps 15 times to form 15 layers of aluminum coating to obtain a finished product; the tension adjustment range is: the tension of the film release end is set to 130N, and the tension of the winding end is set to 100N; the vacuum degree of the vacuum treatment process is 5×10 -3 Pa; The specific evaporation aluminum plating process is as follows: the composite current collector base film is fixed on the winding trolley, the winding trolley is started in a vacuum environment, the winding trolley speed is set to 300m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 500mm / min, and finally a uniform aluminum coating is formed on the composite current collector base film.

[0042] Comparative Example 2: The composite current collector base film is replaced with a PET base film, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: The PET base film is fixed, the film is retracted and released, the tension is adjusted, vacuumed, and evaporated to obtain an aluminum coating, and the above steps are repeated 15 times to form 15 layers of aluminum coating to obtain a finished product; the tension adjustment range is: the tension of the film release end is set to 130N, and the tension of the winding end is set to 100N; the vacuum degree of the vacuum treatment process is 5×10 -3Pa; The specific evaporation aluminum plating process is as follows: the composite current collector base film is fixed on the winding trolley, the winding trolley is started in a vacuum environment, the winding trolley speed is set to 300m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 500mm / min, and finally a uniform aluminum coating is formed on the composite current collector base film.

[0043] Comparative Example 3: The composite current collector substrate film is metallized to obtain a composite current collector substrate film containing a metal oxide layer, and then the composite current collector substrate film containing a metal oxide layer is subjected to an aluminum vapor deposition process 15 times. The rest is the same as Example 1, and the specific steps are as follows: Step 1: The preparation process of heat shrinkable particles is: 90wt% polyethylene terephthalate resin, 5wt% diethylene glycol, and 5wt% acetaldehyde are mixed to obtain a preform; the preform is heated, melted, extruded, stretched from the radial direction into a long strip, and then quickly cooled to room temperature to obtain a strip material; and the strip material is crushed into heat shrinkable particles with a diameter of 25nm;

[0044] In terms of mass fraction, 85wt% polyethylene terephthalate resin, 8wt% stearic acid, 2.5wt% ultrafine calcium carbonate, and 4.5wt% titanate coupling agent are mixed to obtain a polymer layer raw material; 85wt% furan-based polyester, 5wt% stearic acid, 2.5wt% ultrafine calcium carbonate, and 7.5wt% titanate coupling agent are mixed to obtain a modified layer raw material; the polymer layer raw material and the modified layer raw material are prepared by a three-layer co-extrusion process to obtain a film substrate; heat shrinkable particles are sprayed onto the surface of the film substrate, and after cooling, solidification, and pulling, a composite current collector base film is obtained; the film substrate has a polymer layer as an intermediate layer and modified layers on both sides, wherein the thickness of the modified layer is 0.5mm, and the thickness of the polymer layer is 5mm;

[0045] The three-layer co-extrusion process uses the three-layer co-extrusion film blowing technology. The temperature of the outer, middle and inner zones in the film blowing device is set to 220°C, the main engine screw speed is set to 300r / min, the traction speed is 10m / min, and the inflation ratio is 4; spraying parameters: spraying air pressure 40N / cm 2 , gun distance 30cm, spraying temperature 240℃; cooling and curing parameters: cooling roller temperature 30℃, traction force 120N;

[0046] Step 2: Fix the composite current collector base film, retract and release the film, and adjust the tension to obtain a pre-treated composite current collector base film; then evacuate the pre-treated composite current collector base film, evaporate aluminum, and pass oxygen to obtain a composite current collector base film containing a metal oxide layer; the tension adjustment range is: the tension of the film release end is set to 130N, and the tension of the winding end is set to 100N; the vacuum degree of the vacuum treatment process is 5×10 -3Pa; The evaporation aluminum plating process is specifically as follows: the composite current collector substrate is fixed on a winding trolley, the winding trolley is started in a vacuum environment, the winding trolley speed is set to 500m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 80mm / min, and finally a uniform aluminum coating is formed on the composite current collector substrate; oxygen flow parameters: oxygen flow rate 2000sccm;

[0047] Step 3: Fix the composite current collector base film containing the metal oxide layer, retract and release the film, adjust the tension, evacuate, evaporate and aluminum to obtain an aluminum coating, and repeat the above steps 15 times to form 15 layers of aluminum coating to obtain a finished product; the tension adjustment range is: the tension of the film release end is set to 130N, and the tension of the winding end is set to 100N; the vacuum degree of the vacuum treatment process is 5×10 -3 Pa; The specific evaporation aluminum plating process is as follows: the composite current collector base film is fixed on the winding trolley, the winding trolley is started in a vacuum environment, the winding trolley speed is set to 300m / min, the evaporation boat is heated and the aluminum wire is pushed, and the speed of the aluminum wire is set to 500mm / min, and finally a uniform aluminum coating is formed on the composite current collector base film.

[0048] Detection test:

[0049] Tensile strength and elongation test method: cut the composite current collector into strips of 100*15mm; clamp the two ends of the composite current collector strips with a tensile testing machine; the tensile testing machine moves at a constant speed, and when the composite current collector breaks, record the tensile strength and elongation at break; the room temperature tensile strength and elongation at break of the composite aluminum foil are measured using an electronic universal material testing machine, and the test conditions are a gauge length of 10mm, a tensile speed of 100mm / nin, and a width of 15mm. Other requirements are measured according to the method specified in GB / T 1040.3-2006.

[0050] Coating peeling force test: The composite current collector is cut into a test sample with a size of 15mm×100mm, and the 3M-9080A-15mm tape is attached to a stainless steel plate. The measured sample is evenly attached to the double-sided tape and rolled back and forth twice with a 2kg standard small pressure roller. The 3M-9080A-14mm tape is then attached to the surface of the test sample and rolled back and forth twice with a 2kg standard small pressure roller. The pressed test sample is then placed on a tensile testing machine and stretched at 180° for peeling. The speed is 100mm / min and the width is set to 14mm. The peeling strength result takes the maximum value. The peeling strength between the hydrogel layer and the metal layer of the composite current collector before and after ultraviolet light irradiation (ultraviolet light wavelength is 800nm, irradiation time is 10min) is tested.

[0051] Square resistance test: Turn on the power of the square resistance meter and press the probe on the surface of the composite current collector to test the square resistance of the material.

[0052] Active layer peeling force test: The composite current collector after active layer coating was cut into a test sample with a size of 15 mm × 100 mm, and the 3M-9080A-15mm tape was attached to a stainless steel plate, and then the measurement sample was evenly attached to the double-sided tape, and a 2kg standard small pressure roller was used to roll back and forth twice, and then the 3M-9080A-14mm tape was attached to the surface of the test sample, and a 2kg standard small pressure roller was used to roll back and forth twice, and then the pressed test sample was placed on a tensile testing machine and stretched at 180° for peeling, with a speed of 100 mm / min and a width of 14 mm. The peeling strength result was taken as the maximum value, and the peeling strength between the hydrogel layer and the metal layer of the composite current collector was tested before and after ultraviolet light irradiation (ultraviolet light wavelength was 800 nm, and irradiation time was 10 min).

[0053] Composite current collector 25 ℃ electrolyte immersion peeling force test: the surface of the composite current collector soaked in the electrolyte was cleaned with 99.9% alcohol and placed in an oven at 25 ℃ for surface drying; the dried composite current collector was cut to obtain a test sample with a size of 15mm×100mm, and the 3M-9080A-15mm tape was attached to a stainless steel plate, and then the measurement sample was evenly attached to the double-sided tape, and a 2kg standard small pressure roller was used to roll back and forth twice, and then the 3M-9080A-14mm tape was attached to the surface of the test sample, and a 2kg standard small pressure roller was used to roll back and forth twice, and then the pressed test sample was placed on a tensile machine and stretched at 180° for peeling, with a speed of 100mm / min and a width of 14mm. The peel strength result was taken as the maximum value, and the peel strength between the hydrogel layer and the metal layer of the composite current collector before and after ultraviolet light irradiation (ultraviolet light wavelength of 800nm, irradiation time of 10min) was tested. The results are shown in the following table;

[0054] Table 1 Physical properties and peeling force data of composite current collector in Example

[0055]

[0056] Table 2 Stripping force (N / m) of composite current collectors at 25°C electrolysis immersion

[0057] 3 days 7 days 15 days 30 days 60 days Example 1 1786.7 1704.3 1598.5 1441.8 1223.1 Example 2 1692.4 1597.4 1432.1 1298.5 1103.9 Example 3 1784.5 1715.5 1587.1 1469.7 1247.3 Comparative Example 1 1274.4 965.7 562.3 365.9 110.2 Comparative Example 2 1247.3 1078.6 823.6 543.1 358.4 Comparative Example 3 1519.2 1304.1 1044.7 851.9 612.2

[0058] Conclusion: Example 1-Example 2: The square resistance of the composite current collector in Example 2 is significantly higher than that in Example 1;

[0059] Example 1-Example 3: The tensile strength and elongation of the composite current collector in Example 3 are significantly lower than those in Example 1;

[0060] Example 1-Comparative Example 1: Compared with Example 1, the stripping force of the composite current collector coating and the stripping force of the active layer in Comparative Example 1 are significantly reduced; the stripping force after electrolyte immersion is significantly reduced;

[0061] Example 1-Comparative Example 2: Compared with Example 1, the stripping force of the composite current collector coating and the stripping force of the active layer in Comparative Example 2 are significantly lower; the stripping force after electrolyte immersion is significantly lower;

[0062] Example 1-Comparative Example 3: Compared with Example 1, the stripping force of the composite current collector coating and the stripping force of the active layer in Comparative Example 3 are significantly reduced; the stripping force after electrolyte immersion is significantly reduced;

[0063] Example 2-Comparative Example 2: Compared with Example 2, the stripping force of the composite current collector coating and the stripping force of the active layer in Comparative Example 2 are significantly lower; the stripping force after electrolyte immersion is significantly lower;

[0064] Example 3-Comparative Example 3: Compared with Comparative Example 3, the stripping force of the composite current collector coating and the active layer in Example 3 are significantly improved; the stripping force after electrolyte immersion is significantly improved; the tensile strength and elongation of the composite current collector in Example 3 are significantly reduced compared with Comparative Example 3;

[0065] Example 3-Comparative Example 1: Compared with Comparative Example 1, the stripping force of the composite current collector coating and the active layer in Example 3 are significantly improved; the stripping force after electrolyte immersion is significantly improved; the tensile strength and elongation of the composite current collector in Example 3 are significantly reduced compared with Comparative Example 1;

[0066] Example 2-Comparative Example 2: Compared with Comparative Example 2, the stripping force of the composite current collector coating and the active layer in Example 2 are significantly improved; the stripping force after electrolyte immersion is significantly improved.

[0067] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0068] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite current collector base film, characterized in that: The following steps are involved: Polyethylene terephthalate, lubricant, coupling agent and inorganic powder are mixed to obtain polymer layer raw material; furan-based polyester, lubricant, coupling agent and inorganic powder are mixed to obtain modified layer raw material; the polymer layer raw material and modified layer raw material are prepared by three-layer co-extrusion process to obtain a film substrate, wherein the film substrate has a polymer layer as an intermediate layer and modified layers on both sides; heat shrinkable particles are sprayed onto the surface of the film substrate, and after cooling, solidification and pulling, a composite current collector base film is obtained.

2. The method for preparing the composite current collector substrate according to claim 1, characterized in that: The content of each component of the polymer layer raw material is: by mass fraction, 70wt%-90wt% polyethylene terephthalate, 0-8wt% lubricant, 0-2.5wt% inorganic powder, and the balance is a coupling agent; the content of each component of the modified layer raw material is: by mass fraction, 80wt%-90wt% furan-based polyester, 0-10wt% lubricant, 0-3wt% inorganic powder, and the balance is a coupling agent; the lubricant is any one of stearic acid and trihydroxystearin, the coupling agent is a titanate coupling agent, and the inorganic powder is any one of ultrafine calcium carbonate and graphene.

3. The method for preparing the composite current collector substrate according to claim 1, characterized in that: Three-layer co-extrusion process parameters: using three-layer co-extrusion film blowing technology, set the temperature of each section of the outer, middle and inner zones in the film blowing device to 200-220℃, set the main engine screw speed to 240-300r / min, the traction speed to 7-10m / min, and the blowing ratio to 3-4.

4. The method for preparing the composite current collector substrate according to claim 1, characterized in that: The thickness of the modified layer is 0.5-1.0 mm, and the thickness of the polymer layer is 4.0-5.0 mm.

5. The method for making a composite current collector substrate according to claim 1, characterized in that: The preparation process of the heat shrinkable particles is as follows: polyethylene terephthalate resin, diethylene glycol and acetaldehyde are mixed to obtain a prefabricated material; the prefabricated material is heated, melted and extruded, stretched radially into a long strip, and then quickly cooled to room temperature to obtain a strip material; and the strip material is crushed into heat shrinkable particles with a diameter of 10-200nm.

6. The method for making a composite current collector substrate according to claim 1, characterized in that: Spraying parameters: spraying air pressure 25-40N / cm 2 , gun distance 20-30cm, spraying temperature 225-240℃; cooling and curing parameters: cooling roller temperature 20-30℃, traction force 100-120N.

7. A method for preparing a composite current collector, characterized in that: The surfaces of both sides of the composite current collector base film obtained by the manufacturing method described in any one of claims 1 to 6 are subjected to metal plating to obtain a composite current collector; during metal plating, the metal used includes but is not limited to metal copper and metal aluminum; the plating process used includes but is not limited to evaporation process, magnetron sputtering process, electroplating process, and chemical plating process.

8. The method for preparing the composite current collector according to claim 7, characterized in that: The composite current collector base film is fixed on both sides, vacuumized, and aluminum is evaporated on the surface to obtain the composite current collector; the vacuum degree of the vacuum treatment process is 5×10 -3 -5.5×10 -3 Pa; when the surface is evaporated and aluminum is plated, the speed of feeding the aluminum wire is set to 400-500mm / min.

9. A composite current collector, characterized in that: It is produced according to the production method according to any one of claims 7-8.

10. A battery prepared based on the composite current collector according to claim 9, characterized in that: A battery is formed by forming a cathode, an anode, a shell, and an electrolyte layer between the cathode and the anode; The cathode includes a composite current collector and an active material layer coated on the surface of the composite current collector.